Population dynamics of whiteflies and associated viruses in South America: Research progress and perspectives - Krause-Sakate, Renate [UNESP] (2020)
By having an extensive territory and suitable climate conditions, South America is one of the most important agricultural regions in the world, providing different kinds of vegetable products to different regions of the world. However, such favorable conditions for plant production also allow the development of several pests, increasing production costs. Among them, whiteflies (Hemiptera: Aleyrodidae) stand out for their potential for infesting several crops and for being resistant to insecticides, having high rates of reproduction and dispersal, besides their efficient activity as virus vectors. Currently, the most important species occurring in South America are Bemisia afer, Trialeurodes vaporariorum, and the cryptic species Middle East-Asia Minor 1, Mediterranean, and New World, from Bemisia tabaci complex. In this review, a series of studies performed in South America were compiled in an attempt to unify the advances that have been developed in whitefly management in this continent. At first, a background of the current whitefly distribution in South American countries as well as factors affecting them are shown, followed by a background of the whitefly transmitted viruses in South America, addressing their location and association with whiteflies in each country. Afterwards, a series of management strategies are proposed to be implemented in South American fields including cultural practices and biological and chemical finalizing with a section containing future perspectives and directions for further research.